2005
DOI: 10.12702/1984-7033.v05n04a08
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic evaluation and selection of sugarcane clones in three environments in the state of Paraná

Abstract: The objective of this study was to estimate genetic parameters and predict genotypic values in sugarcane clones (series RB96) by the Reml/Blup methodology. The trial was installed in an unbalanced block design to evaluate the yield at three locations in the state of Paraná. The ranking of the clones regarding yield differed from one location to the other, due to the genotypic correlation of intermediate magnitude (0.62) across the locations. The two best clones presented a mean superiority of 28% (RB955466) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 5 publications
1
19
0
7
Order By: Relevance
“…Carbonell et al (2007) reached the same conclusion when comparing these methods in evaluations of common bean lines. Bastos et al (2007) and Oliveira et al (2005) also showed similar results with sugarcane when they compared the MHPRVG, Lin and Binns (1988), and Silva and Duarte (2006) methods, and when they used soybeans to compare the Annicchiarico (1992) and Lin and Binns (1988) methods.…”
Section: Resultsmentioning
confidence: 79%
“…Carbonell et al (2007) reached the same conclusion when comparing these methods in evaluations of common bean lines. Bastos et al (2007) and Oliveira et al (2005) also showed similar results with sugarcane when they compared the MHPRVG, Lin and Binns (1988), and Silva and Duarte (2006) methods, and when they used soybeans to compare the Annicchiarico (1992) and Lin and Binns (1988) methods.…”
Section: Resultsmentioning
confidence: 79%
“…For example Carbonell et al (2007) showed this in the common bean, Borges et al (2010) examined this in rice, and Oliveira et al (2005) analyzed this in sugarcane. Another advantage of HMRP is the possibility of considering more than two N-availability scenarios, making it possible to evaluate stress gradients (Resende, 2004).…”
Section: -------------------------------------------------------% ---mentioning
confidence: 99%
“…ZeniNeto et al (2008) evaluated early maturing sugarcane clones in the State of Paraná by the non-parametric methodology of Lin and Binns (1988). Oliveira et al (2005) and Bastos et al (2007) used mixed models to measure the stability and adaptability of sugarcane clones in the final selection stage.…”
Section: Introductionmentioning
confidence: 99%